2022
DOI: 10.1017/pen.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism-related variations in error processing in a task with increased response selection complexity

Abstract: Perfectionists strive for a flawless performance because they are intrinsically motivated to set and achieve high goals (personal standards perfectionism; PSP) and/or because they are afraid to be negatively evaluated by others (evaluative concern perfectionism; ECP). We investigated the differential relationships of these perfectionism dimensions with performance, post-response adaptation, error processing (reflected by two components of the event-related potential: error/correct negativity – Ne/c; error/corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Other studies, focusing on motivational aspects of error processing showed that the N e varied with the monetary value of errors (Potts, 2011), with the external evaluation of one's performance (Hajcak, Moser, Yeung, & Simons, 2005), with the error context (competitive vs. cooperative context; García Alanis, Baker, Peper, & Chavanon, 2019), and with aversive sounds contingently following errors (Saunders, Milyavskaya, & Inzlicht, 2015). Furthermore, the N e varied with individual differences inherently related to a different error processing motivation like a pronounced behavioural inhibition system (Amodio et al, 2008) and perfectionism (Mattes, Mück, Stahl, 2022a;Stahl, Acharki, Kresimon, Völler, & Gibbons, 2015). Weinberg and colleagues (2012) integrated this diverse literature.…”
Section: The Error Negativitymentioning
confidence: 99%
“…Other studies, focusing on motivational aspects of error processing showed that the N e varied with the monetary value of errors (Potts, 2011), with the external evaluation of one's performance (Hajcak, Moser, Yeung, & Simons, 2005), with the error context (competitive vs. cooperative context; García Alanis, Baker, Peper, & Chavanon, 2019), and with aversive sounds contingently following errors (Saunders, Milyavskaya, & Inzlicht, 2015). Furthermore, the N e varied with individual differences inherently related to a different error processing motivation like a pronounced behavioural inhibition system (Amodio et al, 2008) and perfectionism (Mattes, Mück, Stahl, 2022a;Stahl, Acharki, Kresimon, Völler, & Gibbons, 2015). Weinberg and colleagues (2012) integrated this diverse literature.…”
Section: The Error Negativitymentioning
confidence: 99%